Risk Analysis of Typhoid Fever Based on Personal Hygiene and Street Food Consumption Habit at Home - Hilda Nuruzzaman; Fariani Syahrul (Universitas Airlangga, 2016)
Typhoid fever is disease caused by Salmonella typhi bacteria transmission trought contaminated food and drink. Data from RSUD dr. Abdoer Rahem showing that from 2011-2013 typhoid fever case always increase and often happened to children age 5-14 years old. The objective research to analysis risk factor of typhoid fever according to snacking habit at school and at house of children age 7-12 years old. This research was observasional case control study. Data for case in this research are taken from medical record of 'Unit Teratai' for the past 1 year in RSUD dr. Abdoer Rahem Situbondo, whereas for control are case group. There are eighty person taken for this research as sample. This result was the risk of typhoid fever children which has habit of hand washing had after defecation at home OR 3.67 (1.29 < OR < 10.64), children which has habit of hand washing before eating had OR 4.33 (1.54 < OR < 12.44), children with short dirty fingernails had OR 7.79 (1.46 < OR < 46.18) frequent street food consumption OR 3.89 (1.39 < OR < 11.06), buy snack at food street OR 3.95 (1.40 < OR < 11.30), buy some snack with packing had OR 3.5 (1.26 < OR < 9.38). The conclusion is that habit hand washing after defecation, habit hand washing before eating, short dirty fingernail, frequent food street consumption, buy food street and buy some food with sealed packing can secrease the risk of typhoid fever for children age 7-12 years Keywords: typhoid fever, risk factor of typhoid fever, personal hygiene, street food consumption habit